Prevalence of and factors associated with carbapenem resistant Enterobacterales rectal colonisation in hospitalised neonates in the Western Cape Province, South Africa - Haumann, Michele Esme (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMed)--Stellenbosch University, 2025.